Different bone remodeling levels of trabecular and cortical bone in response to changes in Wnt/β‐catenin signaling in mice. Issue 4 (20th July 2016) - Li, Junfeng; Bao, Quanwei; Chen, Sixu; Liu, Huayu; Feng, Jianquan; Qin, Hao; Li, Ang; Liu, Daocheng; Shen, Yue; Zhao, Yufeng; Zong, Zhaowen
ABSTRACT: Trabecular bone and cortical bone have different bone remodeling levels, and the underlying mechanisms are not fully understood. In the present study, the expression of Wnt/β‐catenin signaling and its downstream molecules along with bone mass in trabecular and cortical bone were compared in wild‐type mice, constitutive activation of β‐catenin (CA‐β‐catenin) mice and β‐catenin deletion mice. It was found that the expression level of most of the examined genes such as Wnt3a, β‐catenin, osteocalcin and RANKL/OPG ratio were significantly higher in trabecular bone than in cortical bone in wild‐type mice. CA‐β‐catenin resulted in up‐regulated expression of the above‐mentioned genes except for RANKL/OPG ratio, which were down‐regulated. Also, CA‐β‐catenin led to increased number of osteoblasts, decreased number of osteoclasts and increased bone mass in both the trabecular bone and cortical bone compared with wild‐type mice; however, the extent of changes was much greater in the trabecular bone than in the cortical bone. By contrast, null β‐catenin led to down‐regulated expression of the above‐mentioned genes except for RANKL/OPG ratio. Furthermore, β‐catenin deletion led to decreased number of osteoblasts, increased number of osteoclasts and decreased bone mass when compared with wild‐type mice. Again, the extent of these changes was more significant in trabecular bone than cortical bone. Taken together, we found that the expression level of Wnt/β‐catenin signaling and bone remodeling‐related molecules were different in cortical bone and trabecular bone, and the trabecular bone was more readily affected by changes in the Wnt/β‐catenin signaling pathway. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:812–819, 2017.